Beyond disorder, danger, incompetence and ignorance: Rethinking the youthful subject of alcohol and other drug policy - Moore, David (Federal Legal Publications, Inc, 2010)
In Australia, as in other parts of the Western world, “binge drinking” and the use of amphetamine-type stimulants among young adults have become high-profile issues in media, policy and research discourses. In these discourses, young adults are frequently characterized as being disordered, dangerous, incompetent, or ignorant, and as either victims of their own “risky” alcohol and other drug consumption or as threats to society as a result of this consumption. In this article, I compare such representations of young alcohol and other drug users with thefindings of three qualitative research projects conducted in the Australian cities of Perth and Melbourne. In contrast to media, policy and research discourses, these projects suggest that in their drinking and other drug use practices, young adults are far from disordered, dangerous, incompetent, or ignorant. These findings, which are consistent with previous qualitative research from Australia, the United Kingdom and Europe, suggest the need to rethink the youthful subject of alcohol and other drug policy.